Translation of nanotechnology-based implants for orthopedic applications: current barriers and future perspective - Chen, Long; Zhou, Chao; Jiang, Chanyi; Huang, Xiaogang; Liu, Zunyong; Zhang, Hengjian; Liang, Wenqing; Zhao, Jiayi (Frontiers in Bioengineering and Biotechnology, 2023)
The objective of bioimplant engineering is to develop biologically compatible materials for restoring, preserving, or altering damaged tissues and/or organ functions. The variety of substances used for orthopedic implant applications has been substantially influenced by modern material technology. Therefore, nanomaterials can mimic the surface properties of normal tissues, including surface chemistry, topography, energy, and wettability. Moreover, the new characteristics of nanomaterials promote their application in sustaining the progression of many tissues. The current review establishes a basis for nanotechnology-driven biomaterials by demonstrating the fundamental design problems that influence the success or failure of an orthopedic graft, cell adhesion, proliferation, antimicrobial/antibacterial activity, and differentiation. In this context, extensive research has been conducted on the nanofunctionalization of biomaterial surfaces to enhance cell adhesion, differentiation, propagation, and implant population with potent antimicrobial activity. The possible nanomaterials applications (in terms of a functional nanocoating or a nanostructured surface) may resolve a variety of issues (such as bacterial adhesion and corrosion) associated with conventional metallic or non-metallic grafts, primarily for optimizing implant procedures.Future developments in orthopedic biomaterials, such as smart biomaterials, porous structures, and 3D implants, show promise for achieving the necessary characteristics and shape of a stimuli-responsive implant. Ultimately, the major barriers to the commercialization of nanotechnology-derived biomaterials are addressed to help overcome the limitations of current orthopedic biomaterials in terms of critical fundamental factors including cost of therapy, quality, pain relief, and implant life. Despite the recent success of nanotechnology, there are significant hurdles that must be overcome before nanomedicine may be applied to orthopedics.The objective of this review was to provide a thorough examination of recent advancements, their commercialization prospects, as well as the challenges and potential perspectives associated with them. This review aims to assist healthcare providers and researchers in extracting relevant data to develop translational research within the field. In addition, it will assist the readers in comprehending the scope and gaps of nanomedicine's applicability in the orthopedics field.